Kedudukan Hukum OJK Dalam Melakukan Pengawasan Terhadap Pinjaman Berbasis Online Melalui Aplikasi Maucash - Ni Kadek Putri Puspita Dewi; H. Djumardin Djumardin; Wahyuddin Wahyuddin (Private Law, 2023)
This study aims to determine the responsibility of the Financial Service Authority (OJK) in supervising online loans and to find out patterns of dispute resolution in the event of default in online loan agreements through the Maucash Application. This type of research is normative-empirical legal research using statutory approaches, conceptual approaches, and sociological approaches. Data collection techniques used library data and field data from interviews which were analyzed descriptively-qualitatively. The results of this study indicate that OJK supervision of MauCash based on POJK Number 77/POJK.01/2016 is divided into two stages, namely pre-operational business and during business operation. For the settlement of default disputes, MauCash forms a Field Collection Team for billing and within 180 days the data will automatically be included in the OJK SLIK.